Hospitalization costs for cervical cancer patients in three tertiary hospitals in northern China, 2013 - 2022: degree of structural variation and gray relational analysis - Mengting WANG; Jian YIN; Yitong ZHU; Tingting ZUO; Bo ZHU; Jia YOU; Wen YANG; Hong WANG; Youlin QIAO; Yuping WANG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo understand the structural variation in hospitalization costs for patients with cervical cancer and to investigate the reasons for these variations. MethodsUsing the degree of structural variation (DSV) analysis and grey relational analysis methods, we analyzed the hospitalization data of 5 654 cervical cancer patients from three class A tertiary hospitals in northern China from 2013 to 2022. The DSV was used to describe the overall characteristics and dynamic trends of the hospitalization cost composition, while gray relational analysis assessed the correlation between hospitalization costs and individual cost items. ResultsDuring this period, the average individual total cost of hospitalization for all patients studied showed an upward trend with a low overall DSV and an average annual DSV of 18.60%. Diagnostic fees and drug costs were two significant factors influencing cost changes. In particular, the structural variation values of diagnostic fees and drug costs showed positive changes during this period. The top three cost items contributing to the change in hospital cost structure were other fees (contribution rate: 35.87%), diagnostic fees (32.09%), and drug costs (16.44%), with a cumulative structural contribution rate of 84.40%. The proportion of diagnostic fees has increased significantly, contributing to the structural variation, indicating that diagnostic fees are a major component of hospitalization costs. Although the proportion of drug costs has decreased in recent years, it remains an important factor influencing cost changes. Gray relation analysis showed that from 2013 to 2022, other fees had the highest correlation with hospitalization costs (correlation coefficient: 0.855), followed by diagnostic fees (0.824) and drug costs (0.781). ConclusionFor the hospitalization costs of cervical cancer patients from tertiary hospitals in northern China, diagnostic fees, drug costs, and other fees contribute significantly to the cost structure and have the highest correlation with hospitalization costs, which are significant factors influencing the fluctuation of hospitalization costs. The structural contribution rates of comprehensive medical service fees and treatment fees are relatively low, and their correlation with hospitalization costs is also lower, so they have minimal impact on the structure and changing trends of hospitalization costs.